The devil's atlas an explorer's guide to heavens, hells and afterworlds - Brooke-Hitching, Edward (London Simon & Schuster UK Ltd, 2021)
"The Devil's Atlas is an illustrated guide to the heavens, hells and lands of the dead as imagined throughout history by cultures and religions around the world. Packed with colourful maps, paintings and captivating stories, the reader is taken on a compelling tour of the geography, history and supernatural populations of the afterworlds of cultures around the globe. Whether it's the thirteen heavens of the Aztecs, the Chinese Taoist netherworld of 'hungry ghosts', or the 'Hell of the Flaming Rooster' of Japanese Buddhist mythology (in which sinners are tormented by an enormous fire-breathing cockerel), The Devil's Atlas gathers together a wonderful variety of beliefs and representations of life after death. A traveller's guide to worlds unseen, The Devil's Atlas is a fascinating study of the boundless capacity of human invention, a visual chronicle of man's hopes, fears and fantasies of what lies beyond"--Publisher's description
Hells and underworlds -- Limbo, purgatory and other midworlds -- Heavens, paradises and utopias.
Includes bibliographical references (pages 246-247) and index
Keywords: Hell; Future Life; Heaven